Aerodynamic analysis of a C-class-like catamaran in simplified unsteady wind conditions using LES and URANS modeling. Issue 180 (September 2018) - Fiumara, Alessandro; Gourdain, Nicolas; Chapin, Vincent; Senter, Julien
Highlights: A numerical analysis on a C-class-like geometry is performed in unsteady wind conditions at different wind frequencies. LES and URANS models agree in predicting the global aerodynamic coefficients as well as the flow structures of the wingsail. Stall cells appear on the wingsail in case of unsteady wind conditions and their features depend on wind frequency. The wind frequency, affecting the stall cells, leads to a modification of the aerodynamic coefficients of the wingsail.